'It was like the unicorn of the therapeutic world': CBT trainee experiences of acquiring skills in guided discovery. (24th June 2022) - Roscoe, Jason; Bates, Elizabeth A.; Blackley, Rhiannon
Abstract: Training as a cognitive behavioural therapist involves a considerable role transition for mental health professionals where they are expected to demonstrate competence in a range of new skills that emphasise collaboration and Socratic dialogue. This can be in stark contrast to the more didactic style that trainees are familiar with prior to embarking on their training. Guided discovery (GD) is an integral part of formulation and treatment, yet little is known at present about the experiences of cognitive behavioural therapy (CBT) trainees when learning this new skill; specifically, how they assimilate this with existing ways of working and the challenges this might involve. This research is a preliminary attempt to understand factors that help and hinder GD skill acquisition. Eighteen trainee CBT practitioners completed an online questionnaire with the subsequent data analysed using a grounded theory methodology. Three themes were identified: 'Competing Selves', 'Style' and 'Active Engagement and Learning'. These themes were used to develop a preliminary model of factors that enable or inhibit skills in GD. The impact of previous professional roles appears to influence the acquisition of confidence and skill in GD. This paper discusses the implications of the findings for CBT trainers, supervisors and trainees. Key learning aims: As a result of reading this paper, readers should: (1) Understand how trainee cognitive behavioural therapists respond to learning how to use guided discovery. (2) Identify potential barriers to acquiring and improving skills in guided discovery. (3) Recognise training strategies that might assist trainees in becoming more proficient in guided discovery.